2018
DOI: 10.1016/j.det.2017.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Rosacea Pathogenesis

Abstract: Rosacea is a chronic inflammatory skin disorder that is not fully understood but involves the complex interplay of genetic factors, immune dysregulation, neurovascular dysregulation, presence of microorganisms, and environmental factors. Increased activation of the immune system occurs through multiple stimuli, including increased levels of cathelicidin and kallikrein 5, Toll-like receptor 2, matrix metalloproteinases, and mast cells within the skin. Their effects are enhanced by the presence of microorganisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
114
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(127 citation statements)
references
References 38 publications
1
114
0
12
Order By: Relevance
“…LL‐37 is a key contributor with kallikrein 5 (KLK5) to immune dysregulation in the skin of patients with rosacea. There are increased levels of MMP‐9 in the skin of patients with rosacea, which may lead to increased KLK5 and LL‐37 levels 30,31 . Thus, matrix metalloproteinase‐9 (MMP‐9) is can be another factor of the possible common etiology.…”
Section: Discussionmentioning
confidence: 99%
“…LL‐37 is a key contributor with kallikrein 5 (KLK5) to immune dysregulation in the skin of patients with rosacea. There are increased levels of MMP‐9 in the skin of patients with rosacea, which may lead to increased KLK5 and LL‐37 levels 30,31 . Thus, matrix metalloproteinase‐9 (MMP‐9) is can be another factor of the possible common etiology.…”
Section: Discussionmentioning
confidence: 99%
“…It is not exactly known whether this altered flora is a consequence of rosacea or it is a trigger for rosacea. Additionally, H.pylori, UV‐A, and UV‐B can also be considered among the other triggering factors …”
Section: Discussionmentioning
confidence: 99%
“…[ 1 – 3 ] These subtypes present with symptoms such as facial erythema, telangiectases, papules, and pustules. [ 22 24 ] And one of the underlying mechanisms of acupuncture is cutaneous neurogenic inflammation changes at acupoints. [ 25 27 ] Thus, these studies suggested that acupuncture could be possibly used to treat the papulopustular and ocular rosacea.…”
Section: Discussionmentioning
confidence: 99%